Addressing the role of internet intermediaries and other stakeholders in the online counterfeit market in South Africa : lessons from selected jurisdictions - Okorie, Chijioke (University of Pretoria, 2025)
Mini-dissertation (LLM (Intellectual Property))--University of Pretoria, 2025.